2012
DOI: 10.2967/jnumed.112.107375
|View full text |Cite
|
Sign up to set email alerts
|

Are Pretreatment 18F-FDG PET Tumor Textural Features in Non–Small Cell Lung Cancer Associated with Response and Survival After Chemoradiotherapy?

Abstract: There is evidence in some solid tumors that textural features of tumoral uptake in 18 F-FDG PET images are associated with response to chemoradiotherapy and survival. We have investigated whether a similar relationship exists in non-small cell lung cancer (NSCLC). Methods: Fifty-three patients (mean age, 65.8 y; 31 men, 22 women) with NSCLC treated with chemoradiotherapy underwent pretreatment 18 F-FDG PET/CT scans. Response was assessed by CT Response Evaluation Criteria in Solid Tumors (RECIST) at 12 wk. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
268
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(296 citation statements)
references
References 34 publications
12
268
3
6
Order By: Relevance
“…This is well consistent with previous studies by texture analysis on MRI and CT scans, which reported that the COM-based texture parameter looks like most valuable parameter for tissue characterization [14,23]. COM-based texture parameter is a kind of second order texture feature which describes neighborhood gray-tone difference, and was generally interpreted to reflect the metabolic heterogeneity of entropy, energy, and contrast of tumor, so that these COM-based texture parameters have high association with tumor pathology stands to reason [17,24].…”
Section: Patientsmentioning
confidence: 66%
See 1 more Smart Citation
“…This is well consistent with previous studies by texture analysis on MRI and CT scans, which reported that the COM-based texture parameter looks like most valuable parameter for tissue characterization [14,23]. COM-based texture parameter is a kind of second order texture feature which describes neighborhood gray-tone difference, and was generally interpreted to reflect the metabolic heterogeneity of entropy, energy, and contrast of tumor, so that these COM-based texture parameters have high association with tumor pathology stands to reason [17,24].…”
Section: Patientsmentioning
confidence: 66%
“…To date, there have been only a few studies investigating the PET texture analysis, and these studies have been localized to prediction of prognosis and evaluation for radiotherapy planning [15]. However, these studies have some ambiguous points about the relationship between textural features and histopathologic characteristics of tumors [17].…”
Section: Patientsmentioning
confidence: 99%
“…There are early reports that textural analysis, an additional tool quantifying intratumoural heterogeneity of 18 FDG-PET tracer uptake, may improve prediction of response and prognosis and it is hypothesised that image heterogeneity may be related to underlying biology and reflect the behaviour of malignant tumours [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Such characterization provides additional and complementary PET image derived quantitative indices with potential value as already demonstrated in predicting therapy response or as prognostic factors in several cancers including lung [16], sarcoma [17], oesophageal [18,19] and rectal cancer [20]. A variety of methodologies has been proposed in order to assess intra-tumour uptake heterogeneity, including visual assessment [21], SUV coefficient of variation (SUVcov) [20], area under the curve of the cumulative histogram (CHAUC) [22] and textural features (TF) analysis [18].…”
mentioning
confidence: 99%